Modelling domestic tourism in Croatia - Baldigara Tea (Turističko Poslovanje, 2018)
The aim of this paper is to use extrapolative models in the attempt to analyse and understand domestic tourism demand flows in Croatia. Such, more detailed and systematic studies should be considered as starting points of future tourism development strategies in Croatia, as a predominantly tourism oriented country. Croatian tourism is predominantly internationally oriented. Nevertheless, domestic tourism demand should be considered more exhaustively in quantitative tourism researches. The present study emphasizes the necessity of more systematic domestic tourism demand determinants quantitative analysis and researches. Econometric modelling and forecasting should be considered as a significant Croatia's tourism sector development tool. The objective of the study is therefore to examine the determinants and the functional form of domestic tourism demand in Croatia. As an approximation of domestic tourism demand, the monthly number of domestic tourist arrivals in Croatia is analysed from January 2005 to December 2017. Modelling and ex post forecasting is performed using some extrapolative models i.e. the seasonal naive model, the seasonal multiplicative Holt-Winters triple exponential smoothing model, the seasonal multiplicative exponential trend model and the seasonal multiplicative integrated autoregression moving average model. Modelling the actual number of monthly domestic tourist arrivals was done for the period from January 2005 to December 2017. Based on the selected forecast models, the ex post forecast of the future value of the monthly number of domestic arrivals was made for the period from January 2018 to September 2018. The statistical diagnostic performance tests of the used models and the analysis of their prognostic efficiency showed that all the models fit well the actual data throughout the entire estimation and forecasting period.